Electrochemical properties of PtRuSn ternary electrocatalyst dispersed on poly (3,4-ethylenedioxythiophene) (PEDOT) for fuel cell application - Suasin, Fe Lourdes P.; Supan, Aaron John M.; Fulo, Harris M.; Garcia, Jonyl L.; Tongol, Bernard John V. (2011)
Fuel cell have been considered as an effective alternative energy source due to its efficient energy conversion and low pollutant emissions. Therefore, improvement in alcohol oxidation is important in fuel cell technology and this can be achieved by developing modified platinum as electrocatalyst. Electrocatalytic oxidation of ethanol in acidic medium was studied using PtRuSn-PEDOT-modified crystalline and (111)-oriented single crystal electrodes of Au and Pt electrodes. In this study, potential cycling from -400 to 850 mV (vs. Ag/AgCl) was employed in depositing the Pt particles. Spontaneous deposition of Ru at 120 seconds with reduction at a constant potential (50mV) was observed to be the most effective method in depositing Ru. This method was also used to deposit Sn particles for the preparation of PtRuSn ternary electrocatalyst. It was observed that 1 mM exhibits the most effective concentration towards ethanol oxidation. The developed ternary electrocatalysts had shown higher electrocatalytic activity by 15.00% - 21.22% than the binary catalysts. The same surface modification methods were employed on Au (111) and Pt (111) single crystal electrodes. It was observed that (111) single crystal substrates exhibit higher electrocatalytic activity by 10.69% [for Au (111)] and 72.63% [for Pt (111)] than their polycrystalline counterparts. As revealed by SEM, PEDOT electrochemically grown on the well-defined single crystal electrode surface was more ordered and smoother than on the polycrystalline substrate. This gave a better dispersion of the eletrocatalysts on the PEDOT matrix, leading to more catalytic active sites.
Keywords: Fuel cells